Evolution, psychology, and technology: Integrative views on social interactions in online environments - Mahfouz, Ahmed Y.; Theocharous, Antonis L.; Philaretou, Andreas Georgiou (My University, 2013)
This study represents an exploratory and quantitative investigation into online dating from evolutionary, psychological, and technological points of view. In the past decade, the relatively inexpensive availability of user-friendly, fast, and reliable Internet technology has appealed to millions of consumers who suddenly found themselves engrossed by this sensational medium of communication, information, consumerism, and service. The majority of Internet users tend to be either recreational or utilitarian oriented, using such medium for a wide variety of tasks ranging from corresponding with friends and significant others, information gathering, purchasing goods and services, and, increasingly so, seeking and securing suitable dating and marital partners. The following research questions constitute the driving force for the current investigation: What are the evolutionary and social psychological intricacies of online dating? What are the technological variants or dimensions that render the consumption of online dating services appealing to users? An online survey was administered to 247 subjects to explore these questions and determine the technological dimensions of virtual social interaction. Exploratory factor analysis was then conducted to analyze the data. Eight technological dimensions emerged as a result of the analysis and served as the basis for the study's technological perspectives model of virtual social interactions.
Keywords: Technology; Social interactions